Heat and mass transfer : fundamentals & applications - Cengel, Yunus A.; Ghajar, Afshin J. (Afshin Jahanshahi), 1951- (Nodia, India : McGraw-Hill, 2015)
With complete coverage of the basic principles of heat ransfer and a broad range of applications in a flexible format, 'Heat and Mass Transfer' provides a blend of fundamental concepts and practical applications.
Includes bibliographical references and index.
Keywords: Heat -- Transmission; Mass transfer